(untitled) - Whitty, Noel; Noel Whitty; Thérèse Murphy; Stephen Livingstone (London,Dayton, Ohio, 2001)
Civil Liberties Law: The Human Rights Act Era is a major new work which charts the ongoing transformation of the civil liberties tradition in the United Kingdom. It explores the euphoria and the scepticism surrounding the introduction of the Human Rights Act 1998 and assesses the value of the new commitment to human rights
Keywords: Civil rights; Civil rights; Civil rights